Aktivitas Antihiperurisemia Ekstrak Tanaman Jelatang (Urtica dioca L.) pada Mencit - Nitya Nurul Fadilah; Susanti Susanti (Health Information : Jurnal Penelitian, 2020)
Hyperuricemia is a high level of uric acid in the blood and can cause gout. One of the drugs used to treat hyperuricemia is allopurinol. The use of these drugs can cause various side effects if used for a long period of time. Nettle plants are known to contain flavonoids which can reduce uric acid levels in the blood. This study was conducted to test the activity of nettle plants and to find out the effective dose in reducing blood uric acid levels in mice. In this study, extracts were made using maceration method using 70% ethanol. Tests were carried out on mice induced by pottasium oxonate and chicken liver juice to increase uric acid levels. Then the test animals were divided into 5 groups cosisted of the negative control group (0.5% NaCMC), positive control (allopurinol 13mg/kgBW), the dose I group (125mg/kgBW), dose II (250mg/kgBW), and dose III (500mg/kgBW). Next step is to measured the decrease of uric acid levels in mice’s blood every hour for 5 hours. Then the data of decreased in uric acid levels were processed statistically using the Anova and Duncan method. Based on the results of test in mice, nettle extract has antihyperuricemia activity with successive doses of 500 mg/kgBW (89.91%), 250 mg/kgBW (73.7%), and 125mg/kgBW (63.56%).